Analysis of the Effect of Diversity of Facilities and Business Locations in Increasing Consumer Interest in the Multibeauty.id Medan - Victor Victor; Agusman Agusman; Cynthia Carolyn (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe the influence of the diversity of facilities and business locations on increasing consumer interest in multibeauty.id salons. This research was conducted for 6 (six) months, starting from September 2023 to February 2024. The respondents of this research were consumers from the multybeauty.id salon, totaling 64 (sixty four) people. The instrument used is a questionnaire to collect data from facility diversity variables, business location variables and business success variables. The data analysis techniques used are validity test, reliability test, descriptive analysis, normality test, multiple linear regression analysis, partial hypothesis test or t test and calculation of the coefficient of determination. The results of the descriptive analysis for the facility diversity variable, business location variable and business interest are in the very good category. Based on partial analysis, the diversity of facilities has a positive and significant effect on increasing consumer interest in the multibeauty.id salon. The business location variable partially has a positive but not significant effect on increasing consumer interest in multibeauty.id salons. Based on a simultaneous analysis of the diversity of facilities and business locations, it has a positive and significant effect on increasing consumer interest in the multibeauty.id salon.